Pengaruh Kombinasi Skarifikasi Dan Perendaman Auksin Terhadap Viabilitas Benih Dan Pertumbuhan Awal Semangka Non Biji (Citrulus Vulgaris Schard L) - Saputra, Bayu; Kurniastuti, Tri; Puspitorini, Palupi (VIABEL: Jurnal Ilmiah Ilmu-Ilmu Pertanian, 2017)
Watermelon cultivation has problems of seed germination. Seeds of watermelon that immediately sowing will slow in germinating, not even germinate at all. This is caused by the dormancy period of seeds, which is wrapped in seed institutions by the skin layer. Currently there has been considerable effort to improve seed viability, one using scarification techniques and soaking treatment of growth regulators. Based on the description above, the research is conducted to find out the influence of seed cutting and the effect of the old Atonic immersion on seed viability and growth of watermelon seed (Citrullus vulgaris, Schard). The method used in this research is Randomized Block Design (RAK). The first factor was no breaking (P1) and with the breaking of the seed shell (P2), the second factor was 4 long Atonic immersion (J1 = 0 min, J2 = 45 min, J3 = 90 min, and J4 = 135 min) with 3 repetitions. The Atonic concentration used is 1 ml / l of water. So there are 8 treatment combinations and 24 experimental units. Based on the results of the research, the following conclusions can be obtained: 1) there is the best combination between watermelon seedlings and duration of immersion of Auksin on viability and growth of non-seedled watermelon plants (Citrullus vulgaris), 2) Scarification combination and immersion time Auksin 45 minutes (P2J2) watermelon non seeds showed a very significant effect on seed viability and other observation variables up to 35 hst. 3) combination of scarification and duration of immersion of 45 to 90 minutes with 1 ml of perliter concentration potentially increase the viability and growth of seed seedling watermelon.